Nanotheranostics with gold nanoparticles applied to Radiotherapy - Soares, Sílvia (2021)
Sílvia Soares is grateful for the financial support of Fundação para a Ciência e Tecnologia (grant reference: SFRH/BD/138271/2018) and thanks the kind collaboration of all those involved in the radiotherapy service at Centro Hospitalar Universitário de São João for carrying out radiotherapy treatments.